Comparison of Gonadal Development in Diploid and Triploid Hybrid Groupers, Epinephelus coioides♀ × Epinephelus lanceolatus♂. Issue 2 (12th January 2018) - Li, Shuisheng; Liu, Qiongyu; Xiao, Ling; Tao, Min; Shu, Hu; Zhang, Haifa; Lin, Haoran; Zhang, Yong
Abstract: In this study, the gonadal development of 10‐ to 43‐mo‐old diploid and triploid orange‐giant grouper hybrids, Epinephelus coioides ♀ × Epinephelus lanceolatus ♂, was investigated. The diploid hybrid groupers exhibited normal gonadal development and experienced vitellogenesis at 43 mo of age. In contrast, the triploid gonad was masculinized and gradually filled with spermatogenic cysts. Radioimmunoassays revealed that the diploid hybrids showed high serum E2 levels at 10 and 43 mo and high T levels at 43 mo, while the triploid hybrids showed high E2 levels at 18 and 30 mo and high T levels at 18 mo. Furthermore, the messenger RNA (mRNA) expression of genes related to reproductive regulation was examined in these hybrids. The mRNA levels of fshb, fshr, lhb, lhr, dmrt1, and sox9 varied significantly during gonadal development. Interestingly, the expression levels of fshr, lhr, dmrt1, and sox9 were higher in triploid hybrids than in diploid hybrids. The hyperactive expression of these genes may be associated with the gonadal masculinization of triploid hybrids.